Princess Posey and the perfect present - Greene, Stephanie (Greene, Stephanie. Princess Posey, first grader, 2011)
For first-grader Posey, every school day is great until her teacher's birthday, when her best friend's gift of an enormous bouquet puts Posey's few, home-grown roses to shame.